Inflammation in Periodontal Disease: Possible Link to Vascular Disease - Paul, Oindrila; Arora, Payal; Mayer, Michael; Chatterjee, Shampa (Frontiers in Physiology, 2021)
Inflammation is a well-organized protective response to pathogens and consists of immune cell recruitment into areas of infection. Inflammation either clears pathogens and gets resolved leading to tissue healing or remains predominantly unresolved triggering pathological processes in organs. Periodontal disease (PD) that is initiated by specific bacteria also triggers production of inflammatory mediators. These processes lead to loss of tissue structure and function. In addition to localized damage to gum tissue, periodontal inflammation is a risk factor for systemic inflammation and eventually cardiovascular disease (CVD). This review discusses the role of inflammation in PD and its two way association with other health conditions such as diabetes and CVD. Some of the mechanisms underpinning the links between inflammation, diabetes, CVD and PD are also discussed. Finally we review available epidemiological data and other reports to assess possible links between oral health and cardiovascular disease.